Bias Gender Dalam Perceraian (Studi Perbandingan antara Talak dan Cerai Gugat) - Sopyan, Yayan (Musawa Jurnal Studi Gender dan Islam, 2004)
Islam respects the existence of marriage institutions and terms marriage as a strong bound (misthaqan ghaliza) that has to be looked after. However, Islam allows married couples who have some reasonable arguments to get a divorce albeit this is not a preferable deed. InIslam, divorce could be initiated by either husband (talaq) or wife (khulu'). This article is an attempt at discussing the question of divorce in Islam, focusing on the issues of talaq and khulu'. It then discusses how the divorce proceedings are implemented at Religious Courts in Indonesia.